Continuous enteral nutrition compared with a maximal gastric vacuity strategy at the time of extubation in the intensive care unit: protocol for a non-inferiority cluster randomised trial (the Ambroisie Project) - Bruno Giraudeau; Stephan Ehrmann; Arnaud W Thille; Alain Robert; Mai-Anh Nay; Elsa Tavernier; Jean Reignier; Mickael Landais; Johann Auchabie; Noemie Hubert; Anne Rebion (BMJ Open)
Introduction Fasting is frequently imposed to patients before extubation in the intensive care unit based on scheduled surgery guidelines. This practice has never been evaluated among critically ill patients and may delay extubation, increase nursing workload and reduce caloric intake. We are hypothesising that continuous enteral nutrition until extubation represents a safe alternative compared with fasting prior to extubation in the intensive care unit.Methods and analysis Adult patients ventilated more than 48 hours and receiving pre-pyloric enteral nutrition for more than 24 hours are included in this open-label cluster randomised parallel group non-inferiority trial. The participating centres are randomised allocated to continued enteral nutrition until extubation or 6-hour fasting (with concomitant gastric suctioning when feasible) prior to extubation. The primary outcome is extubation failure (ie, reintubation within 7 days following extubation).Ethics and dissemination This study has been approved by the national ethics review board (comité de protection, des personnes Sud Mediterranée III No 2017.10.02 bis) and patients are included after informed consent. Results will be submitted for publication in peer-reviewed journals.Trial registration number ClinicalTrials.gov Registry (NCT03335345).